Training effectiveness: factors that influence learning and transfer of training at higher learning institution at Klang Valley / Masliana Tamrin, Noor Azzura Mohamed and Nurul Aida Harun - Tamrin, Masliana; Mohamed, Noor Azzura; Harun, Nurul Aida (Research Management Institute (RMI), 2012)
Nowadays the marketplace for talented and skills people is very competitive and expensive. The organization needs to invest through the education and training program. Through training programs, organization can improve and maintain the quality of their human capital. Employees are known as the assets for the company so it is essentially for each organization to have their own training program for the new and existing employees. Education is a never ending process and it is the reason training is been used as it can improve employee performance and directly it can improve business result. Training is one of the education processes which can increase the capabilities and expertise of employees in performing their duties. Training must be continuously given to employees so that it can provide them the knowledge and skills they require to be successful. Wei Tao (2006) mentioned in his study that through the sufficient training given by the organization, it can increase the adaptability and flexibility of workers in doing their work. By having training, it can lead employees to learn new information, they can revise what they have learned before and also they can strengthen their existing knowledge and skills relating to their works. Management must give effective trainings from time to time in order to transmit all relevant and valuable information that can enlighten employees and increase their skills and behaviors so that the knowledge and information they get during the training can be transferred back to the workplace. It is the goal of training to get employees to master the knowledge, skills and behavior so that it can be applied in their daily working activities. Besides that, training also requires the support from the environment's growth and development to ensure for its success.